Penerapan Media Poster untuk Meningkatkan Rasa Kepedulian Siswa terhadap Lingkungan Madrasah Ibtidaiyah Al-Munawwarah Kota Jambi - Enil Elidia; Tabroni Tabroni (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study aims to enhance students' environmental awareness through the implementation of poster media in Natural and Social Sciences (IPAS) learning at Madrasah Ibtidaiyah Al-Munawwarah Kota Jambi. This research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles. The subjects of this study were sixth-grade students. The results indicate an improvement in students' environmental awareness after implementing poster media. In the pre-cycle stage, students’ environmental awareness was only 12%. After implementing poster media, the percentage increased to 60% in the first cycle and reached 96% in the second cycle. Furthermore, teacher activity in the learning process improved from 73.8% in cycle I to 92.6% in cycle II, while student activity increased from 71.5% to 92.1%. These findings demonstrate that poster media can be an effective learning tool in fostering students’ awareness and concern for their school environment.